(untitled) (Nativa, 2024)
ABSTRACT: The current study was completed in Salah al-Din Governorate for a full year, the period extending from June 2022 until the end of May 2023, to evaluate the concentration of zinc and copper in the plants adjacent to the Tigris River. It included the selection of six sites within the governorate, taking into account the locations close to the sources of pollution with heavy metals and the direct effects of population centers, which are (Al-Boujwari village, Al-Hajjaj village, Wadi Sheshin area, Al-Balaj, Al-Alam district and Al-Mahzam area); plant samples were taken three times for each site, during the four seasons of the year. The results showed that the concentrations of heavy metals varied temporally and spatially, as the values ​​of zinc and copper ranged between (0.62-0.04) (0.52-0.02) mg L-1, respectively. An increase in zinc concentrations was observed compared to copper, and an increase in most concentrations was observed in the summer compared to other seasons. Keywords: heavy metals; zinc; copper; plants pollution. Avaliação das concentrações de alguns metais pesados em plantas adjacentes ao rio Tigris, Iraque RESUMO: O presente estudo foi concluído na província de Salah al-Din, durante um ano inteiro, durante o período que se estende de junho de 2022 até o final de maio de 2023, para avaliar a concentração de alguns metais pesados, zinco e cobre nas usinas adjacentes ao rio Tigre. Incluiu a seleção de seis locais dentro da província, tendo em conta os locais próximos das fontes de poluição com metais pesados e os efeitos diretos dos centros populacionais, que são (aldeia Al-Boujwari, aldeia Al-Hajjaj, área de Wadi Sheshin, Al-Balaj, distrito de Al-Alam e área de Al-Mahzam), foram colhidas amostras de plantas três vezes para cada local, durante as quatro estações do ano. Os resultados do estudo mostraram que as concentrações de metais pesados variaram temporal e espacialmente, já que os valores de zinco e cobre variaram entre (0,62-0,04) (0,52-0,02) mg L-1, respectivamente. Foi observada uma taxa de aumento das concentrações de zinco em comparação com o cobre e aumento na maioria das concentrações no verão em comparação com outras estações. Palavras-chave: Metais pesados; zinco; cobre; poluição de plantas.